Counseling the Important Role of Family in the Cares of Patients with Mental Disorders as an Effort to Prevent Relapse - Muhammad Haris Firdausi; Tansa Hadi Bentari; Rizky Noni Amalia; Izzatun Nafis ZP; Hani Mufidatul Khoiriah (Universitas Muhammadiyah Malang, 2025)
Background: Recurrence is the return of a disease after the symptoms of the disease have subsided until it is severe enough to interfere with daily activities and requires unscheduled hospitalization/walking. Lack of social and family support is one of the causes of relapse. The family is the main support system in providing direct care to someone with mental illness. If the family has resilience, they can cope with stress and provide care for ODGJ to prevent relapse. Purpose: To increase the knowledge of the community, especially families, about the role of the family in patient care as an eﬀort to prevent relapse of patients with mental disorders. Methods: The method used is a descriptive data analysis technique which compares the total correct and incorrect answers in each statement between the questionnaire before and after counseling. Results: The results obtained before counseling were 20% of families understood the trigger and prevention of relapse for patients with mental disorders, while after counseling 80% of families understood the trigger and prevention of relapse for patients with mental disorders. Conclusion: There is an increase in family knowledge in patient care as an eﬀort to prevent relapse of patients with mental disorders.